Планарные LC-резонаторы с распределенными параметрами и их применение - Negodenko, O. N.; Sementsov, V. I.; Khvostenko, A. A.; Zaruba, D. V. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
The design of an LC resonator with distributed parameters is presented. Equivalent circuits of the resonator are obtained for different connection options. It is shown that at frequencies below the cutoff, the resonator can be represented by a parallel or series equivalent circuit consisting of lumped inductance and capacitance. Examples of using LC resonators with distributed parameters are given, including in an electromagnetic radiation sensor for receiving television signals and in a radio-pair sensor.